ASAS PERBEZAAN KADAR DIYAT ANTARA LELAKI DAN WANITA MENURUT UNDANG-UNDANG ISLAM - Ismail, Paizah (Jurnal Syariah, 2019)
Diyat or compensation is elaborated by the fllqaha as the amount compensated by the party committing the offence of killing or harming to the victim or his fqmily whether the offence is committed with intention or by accident. Based on various authoritative sources, an attempt is made to establish the actual amount to be paid to the victim, male or female.